The invisibility of heterosexuality in HIV/AIDS prevention for men - Andréa Fachel Leal; Daniela Riva Knauth; Márcia Thereza Couto (Revista Brasileira de Epidemiologia, 2015)
ABSTRACTHeterosexual men have been a forgotten group for HIV/AIDS interventions and research. Our goal was to identify the different elements that interfere in the prevention of HIV/AIDS among heterosexual men, covering both traditional methods of prevention (especially safe sex practices and testing) and new strategies for prevention (pre- and post-sexual exposure prophylaxis, prevention treatment, and circumcision) in this population. This exploratory article consists of a nonsystematic review of the literature. We discuss the invisibility of heterosexual men in policies, in programs, and in health services. The several interventions analyzed are still poorly monitored and evaluated, so there is a lack of consistent evidence regarding the impact of prevention strategies in this population. Different masculinities, including hegemonic conceptions of masculinity, must be the foundation for interventions targeting men. Men must not be seen merely as a "bridge" in the spread of the HIV/AIDS epidemic, but also as victims of gender patterns that make them vulnerable.